PENGEMBANGAN LEMBAR KERJA MAHASISWA MODEL ADVANCED ORGANIZER PADA MATA KULIAH ALJABAR LINEAR ELEMENTER - Yosepha Patricia Wua Laja; Zulkaidah Nur Ahzan (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The problem is that there is disequilibrium between old knowledge and new knowledge which makes mathematics education students difficult to study material on systems of linear equations in elementary linear algebra courses. Therefore, they need media that can facilitate old knowledge and new knowledge so that knowledge is equilibrium. One of the media that can be used is the advanced organizer student worksheet. The aim of this research is to produce an advance organizer model student worksheet that is valid, practical and effective. This research is development research using the ADDIE model (analysis, design, development, implementation and evaluation). At the analysis stage, needs analysis, material analysis and learning environment analysis are carried out. At the design stage, an LKM is created which has four characteristics, namely identity, presentation of an advance organizer, presentation of the main material and practice questions to strengthen the schema or cognitive structure. Then at the development stage, the LKM that has been designed is validated by experts. Then at the implementation stage, small trials are carried out to get practical LKM and large class trials to get effective LKM. Then the evaluation stage concerns the things that need to be evaluated in the LKM. After going through this research stage, the results were conclude that 87.72% valid, 94.84% practical and 59% effective for student learning outcomes.